ITO/Polymer matrix assisted surface plasmon resonance based fiber optic sensor - Satyendra Kumar Mishra; Akhilesh Kumar Mishra (Results in Optics, 2021)
Owing to the ease of implementation, the field of surface plasmon resonance (SPR) based sensors are seeing a surge of research interest from last two decades. In this paper, we present and numerically characterize a simple SPR based fiber optic refractive index sensing probe. The sensing probe utilizes a layer of indium tin oxide (ITO) and polymer matrix on the bare core of a multimoded fiber. The polymer is a combination of poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA). The film of ITO induces plasmonic excitation and the polymer matrix of PAH/PAA enhances the sensitivity and figure of merit of the device. Moreover, the coating of polymer materials over ITO is not time consuming and can easily be processed by dip coating. The optimum values of the sensitivity, DA, and FoM as exhibited by the sensing probe are respectively 10.28 µm/refractive index unit (RIU), 2.62 µm−1, and 22.07 RIU−1 for analyte refractive indices (RIs) varying between 1.33 and 1.38 RIU.